Effects of cold exposure on metabolites in brown adipose tissue of rats - Yuka Hiroshima; Takenori Yamamoto; Masahiro Watanabe; Yoshinobu Baba; Yasuo Shinohara (Molecular Genetics and Metabolism Reports, 2018)
Brown adipose tissue (BAT) plays an important role in regulation of energy expenditure while adapting to a cold environment. BAT thermogenesis depends on uncoupling protein 1 (UCP1), which is expressed in the inner mitochondrial membranes of BAT. Gene expression profiles induced by cold exposure in BAT have been studied, but the metabolomic biological pathway that contributes to the activation of thermogenesis in BAT remains unclear. In this study, we comprehensively compared the relative levels of metabolites between the BAT of rats kept at room temperature (22 °C) and of those exposed to a cold temperature (4 °C) for 48 h using capillary electrophoresis (CE) time-of-flight mass spectrometry (TOFMS) and liquid chromatography (LC)-TOFMS. We identified 218 metabolites (137 cations and 81 anions) by CE-TOFMS and detected 81 metabolites (47 positive and 34 negative) by LC-TOFMS in BAT. We found that cold exposure highly influenced the BAT metabolome. We showed that the cold environment lead to lower levels of glycolysis and gluconeogenesis intermediates and higher levels of the tricarboxylic acid (TCA) cycle metabolites, fatty acids, and acyl-carnitine metabolites than control conditions in the BAT of rats. These results indicate that glycolysis and β-oxidation of fatty acids in BAT are positive biological pathways that contribute to the activation of thermogenesis by cold exposure, thereby facilitating the generation of heat by UCP1. These data provide useful information for understanding the basal metabolic functions of BAT thermogenesis in rats in response to cold exposure. Keywords: Brown adipose tissue, Metabolomics, Cold exposure